2016
DOI: 10.1186/s12866-016-0650-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, characterization, and antibiotic susceptibility of Vibrio parahaemolyticus isolated from retail aquatic products in North China

Abstract: BackgroundVibrio parahaemolyticus is a major foodborne pathogen, particularly in Asian countries. Increased occurrence of outbreaks of V. parahaemolyticus gastroenteritis in China indicates the need to evaluation of the prevalence of this pathogenic species. V. parahaemolyticus distribution in shellfish from the eastern coast of China has been reported previously. However, to date, the prevalence of V. parahaemolyticus in retail aquatic products in North China has not been determined. To investigate the preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
44
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 57 publications
14
44
5
Order By: Relevance
“…The general trend of season variation of the frequency of occurrence of Vibrio parahaemolyticus showed that shrimps in the wet season were more contaminated with Vibrio parahaemolyticus than those of the dry season. This finding contrast the findings of Xu et al [51] who reported high isolation rate of Vibrio parahaemolyticus in aquatic products in summer (50%) and 22.7% in winter.…”
Section: Discussioncontrasting
confidence: 57%
“…The general trend of season variation of the frequency of occurrence of Vibrio parahaemolyticus showed that shrimps in the wet season were more contaminated with Vibrio parahaemolyticus than those of the dry season. This finding contrast the findings of Xu et al [51] who reported high isolation rate of Vibrio parahaemolyticus in aquatic products in summer (50%) and 22.7% in winter.…”
Section: Discussioncontrasting
confidence: 57%
“…De Melo et al (2011) reported that in antibiotic susceptibility test five strains (50%) presented multiple antibiotic resistant to ampicillin (90%) and Amikacin (60%), while two strains (20%) displayed intermediate-level of resistance to Amikacin. Xu et al (2016) reported the antimicrobial resistance patterns of 145 isolates of V. parahaemolyticus to 12 antimicrobial agents revealed that most of the isolates resistant to streptomycin, with resistance and intermediate rates of 86.2 % and 11.7 %, respectively. In addition, the isolates exhibited relatively high resistance rates, of 49.6 %, 43.5 %, 35.9 %, and 22.1 %, for ampicillin, cefazolin, cephalothin, and kanamycin, respectively.…”
Section: Bpmentioning
confidence: 99%
“…The strain VH3 was found to possess multidrug resistance efflux pumps and antibiotic resistant genes for fluoroquinolones and tetracycline [75] . Moreover, V. parahaemolyticus has also been reported to be resistant to numerous classes of antibiotics such as penicillins (ampicillin), aminoglycosides (amikacin, kanamycin, streptomycin), cephalosporins (cefotaxime, ceftazidime, cefazolin) [76,77] , quinolones (ciprofloxacin, nalidixic acid), macrolides (azithromycin, erythromycin) and chloramphenicol [78,79] .…”
Section: Emergence Of Antibiotic Resistant Vibrio Spmentioning
confidence: 99%